Regulation and Compliance in Japanese Financial Institutions - Karai, Akiko (Columbia Journal of Asian Law, 2001)
In January 1999, forty inspectors of the Japanese Financial Supervisory Agency (“FSA”)l marched into the offices of the Credit Suisse First Boston (“CSFB”) group in Tokyo for a surprise inspection aimed at uncovering loss-concealing transactions the group provided to its clients. After six months of investigation, the FSA announced a severe final penalty to the group, including the revocation of the banking license of Credit Suisse Financial Products (“CSFP”), the group’s derivatives arm. The FSA’s stated reasons for the sanction were CSFB’s provision of window dressing transactions “extremely inappropriate from the standpoint of adequate disclosure of its clients’ financial conditions,” “systematic evasions and obstructions of inspections” such as shredding and hiding documents, and violation of firewall regulations. The FSA also posed administrative action to several other foreign financial institutions, including Deutsche Securities, because of window dressing transactions. This series of administrative actions, best represented by the actions against CSFB, present an interesting issue. The administrative actions certainly demonstrate the improvement of the FSA’s inspection capability, signifying one of the achievements of the ongoing financial reformation. However, more than that, what has happened between the FSA and the foreign financial institutions provides an interesting case on future relations between the FSA and Japanese financial institutions. The CSFB incident was unique since a major part of the market was reaching the same understanding on the legality of a certain product that was not consistent with the understanding of regulators. Again, this happened because communication between foreign financial institutions and financial regulators was precisely what it was supposed to be under the new financial regulatory structure. Unlike Japanese financial institutions that have enjoyed a close relationship with regulators, foreign financial institutions have been on their own. While Japanese financial institutions dare not provide a new product without first discussing it with regulators, foreign financial institutions (having input from legal counsel, accountants and other advisors), structured new products without it being necessary to discuss the product with the regulator. But the administrative action by the FSA was over a product developed in just such a way. The FSA has been changing its attitude toward Japanese financial institutions under a principle of “fair and transparent financial supervisory.” Now that prior counseling is not always available from regulators, Japanese financial institutions must also conduct due diligence on the appropriateness of a product. In such situations, an incident similar to what happened to CSFB, Deutsche Securities, and several other foreign financial institutions may happen to Japanese financial institutions, involving an inconsistent approach to an issue between the financial regulator and financial institutions. By studying the CFSB incident, it may be possible to improve the regulatory situation, and avoid the same mistakes.